Scientific publications about errors in medication administration in online nursing journals: a review article - Cleide Rejane Damaso de Araújo; Solange Fátima Geraldo da Costa; Alana Tamar Oliveira de Sousa; Maria Miriam Lima da Nóbrega (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
Problem: In healthcare services, it is the responsibility of the nursing staff to administer drugs. With the growing advances in new drug availability within the pharmaceutical industry, medicative practices have become complex, which contributes to the error rate. Objective: The objective of this article is to investigate, in online nursing journals, scientific publications involving errors in medication administration. Method: It is a bibliographical study that sampled eighteen articles from five nursing journals available in the Scientific Electronic Library Online (SciELO) database for the period of 2000 and 2008.  Results: The data was collected in May 2009 and analyzed using a content analysis technique. The guideline category was errors in the medication administration and three subcategories: types, causes and consequences; nursing professionals' behaviors, conduct and feelings; prevention proposals. It was seen that, quantitatively, the largest number of publications corresponded to the third subcategory, which denotes the authors' concern with the subject. Conclusion: The articles analyzed are directly related to nursing aid practices in the context of drug administration, with emphasis on error occurrence. The study's empiric material identified the types, causes and consequences of errors, as well as the conduct, behaviors and feelings of the nursing professionals, and preventive measures related to the problem.